Living on the frontier of Catholicism: Graham Greene's disloyal conversions. (2nd January 2019) - Valverde, Beatriz; Bosco, Mark
ABSTRACT: Graham Greene's novels are often discussed – and evaluated – in light of the author's religious preoccupations. As Greene was a convert to the Catholic faith from a nominal Anglican upbringing, critics have often addressed the representation of Catholicism in his work as an alternative – and minority – discourse of modernity, trying to categorize his religious affiliations and utilizing his theological concerns as a means of interpreting the moral discourse of his narratives. Moving beyond the debate of such categorizations, in this paper the authors examine Greene's conversion as an individualized process, reconsidering his religious conversion through an analysis of one of the key paradoxes that extends throughout all of Greene's work: his sustained argument for the 'virtue of disloyalty' found in both his essays and novels. Through the lens of Yuri Lotman's cultural semiotic theory and, concretely, his notion of the frontier, this essay suggests a fresh understanding of the role that his conversion played in his developing moral and political vision. By focusing on four of Greene's major novels, The Power and the Glory, A Burnt-Out Case, The Honorary Consul and Monsignor Quixote, the authors examine how Greene apprehends the frontiers of his Catholic faith.